Training and Providing Psychological Motivation to Traders Reduce Trading Risks: Pelatihan Dan Pemberian Motivasi Psikologis Pada Trader Mengurangi Resiko Trading - Iola Riris Simanjuntak; Supriyono (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Trading psychology refers to the emotions and mental states that help determine success or failure in securities trading. Implementing training and providing motivation is very necessary in futures companies as one of the success factors in trading. This method focuses more on the human element. Theoretical applied activities in internship practice are carried out at the Agrodana Futures company. The aim of the activity is to observe and analyze applied training and trading psychology for traders. The analysis results show that training and providing motivation can help reduce trading risks. Comprehensive training and strong motivation, significantly contribute to controlling emotions, making more rational decisions, and ultimately lowering the level of trading risk. Comprehensive training and strong motivation are considered key elements in forming a stable mentality and responsiveness to market dynamics in improving the performance and business sustainability of the futures trading industry.